Clinical features of rheumatoid arthritis-associated interstitial lung disease - Wang, Ting (Sci Rep, 2015)
Interstitial lung disease (ILD) is the most common extra-articular manifestations of rheumatoid arthritis (RA) in the lung. This study aimed to identify clinical features of RA-associated ILD (RA-ILD). Patients with RA were retrospectively enrolled and sub-classified as RA-ILD or RA without ILD based on high-resolution computed tomography imaging. Pulmonary function testing parameters and levels of RA-related biomarkers, tumour markers, and acute-phase proteins were compared between the two groups. Logistic regression model was used to assess the strength of association between RA-ILD and clinical features of interest. Receiver operating characteristic analysis was performed to assess potential predictive value of clinical features for detecting RA-ILD. Comparison analysis indicated that the percentage of predicted value of total lung capacity, inspiratory capacity, and diffusion capacity of the lung for carbon monoxide (DLCO) were reduced in patients with RA-ILD. Tumour markers CA15–3 and CA125 were increased in patients with RA-ILD. Logistic regression analysis revealed that decreased DLCO was related to the increased likelihood of RA-ILD (OR = 0.94, 95%CI = [0.91, 0.98]). The cut-off point at 52.95 percent of predicted value could sensitively discriminate RA patients with or without ILD. Our study suggested that DLCO value could be a useful tool for detecting ILD in patients with RA.